2002
DOI: 10.1038/sj.bjc.6600653
|View full text |Cite
|
Sign up to set email alerts
|

PTEN/MMAC1 expression in melanoma resection specimens

Abstract: PTEN/MMAC1, a tumour suppressor gene located on chromosome 10q23.3, has been found to be deleted in several types of human malignancies. As the chromosomal region 10q22-qter commonly is affected by losses in melanomas, we addressed this gene as tumour suppressor candidate in melanomas. Investigating PTEN/MMAC1 expression at mRNA level by semiquantitative reverse transcription-polymerase chain reaction, we did not find a statistically significant down-regulation in melanoma resection specimens in comparison to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…This contrasts with Dictyostelium cells, in which around 10% of PTEN associates the cell perimeter after chemoattractant stimulation (Iijima and Devreotes, 2002). Our data are nonetheless consistent with other studies in mammalian cells, which indicate that the bulk of PTEN is in the cytoplasm and/or nucleus (Deichmann et al, 2002;Gimm et al, 2000;Wu et al, 2000). The mechanisms regulating PTEN activity and subcellular distribution are not yet fully known.…”
Section: Discussionsupporting
confidence: 83%
“…This contrasts with Dictyostelium cells, in which around 10% of PTEN associates the cell perimeter after chemoattractant stimulation (Iijima and Devreotes, 2002). Our data are nonetheless consistent with other studies in mammalian cells, which indicate that the bulk of PTEN is in the cytoplasm and/or nucleus (Deichmann et al, 2002;Gimm et al, 2000;Wu et al, 2000). The mechanisms regulating PTEN activity and subcellular distribution are not yet fully known.…”
Section: Discussionsupporting
confidence: 83%
“…For the P38S variant, already reported (Guldberg et al, 1997), only the mutated allele was detected, suggesting that the wild-type allele has been deleted. The P246S missense mutation is a novel variant ( Figure 1b); it affects a region next to phosphate acceptor sites (residues 233-240) possibly altering the PTEN protein function (Deichmann et al, 2002). A third PTEN point mutation leading to a substitution of cysteine by arginine at position 105 was detected in one sample (30966 M) in association with a deletion (T313C þ 314delT) inducing a frame shift and a novel stop codon in position 112 (C105fsX112).…”
Section: Pten Genementioning
confidence: 99%
“…117,118 PTEN is another tumor suppressor gene that is also involved in the phosphatidylinositol-3 kinase pathway that does not distinguish benign nevi from melanoma. [119][120][121] Ilmonen et al 122 describe ezrin, a 70 kDa protein involved in the phosphatidylinositol-3 kinase pathway, and report its expression to be inversely correlated with survival in 95 melanomas studied, although the correlation did not reach statistical significance.…”
Section: Signaling Moleculesmentioning
confidence: 99%
“…The p75 nerve growth factor receptor, a 75 kDa protein which functions as a low affinity receptor for nerve growth factor, was found by Kanik et al 52 to be positive in 10/13 spindle cell melanomas and only 3/8 non-spindle cell melanomas. They also reported that p75 was positive in 5/5 Ôneurotized' nevi, nevi that have undergone neural/ Dai et al 117 reported Akt as an independent risk factor in thin melanomas PTEN No distinction between nevi and melanomas [119][120][121] Ezrin No distinction between nevi and melanomas 122 Ilmonen et al 122 report statistically insignificant inverse correlation between positive staining and survival Fig. 1.…”
Section: P27mentioning
confidence: 99%